THE PROGRAM FOR PREVENTION OF CHRONIC NON-INFECTIOUS DISEASES IN JSC "SBERBANK OF RUSSIA": SYNTHESIS OF EVIDENCE-BASED MEDICINE AND MARKETING TECHNOLOGIES - A. V. Kontsevaya (Российский кардиологический журнал)
The article describes a program for CNID prevention, made up in 2011-2013 in JSC Sberbank of Russia. The description is given for the main components of the program, including medical part, that aimed early CNID screening and decrease of complication development risk; and marketing part, aimed on promotion of healthy life style with use of modern marketing technologies. The data provided on efficacy of the program at temporary invalidity costs, and increase of emplyer reputation. At the end the article concerns on brief review of complications occuring during program performing in a gross bank.